Properdin Deficiency Impairs Phagocytosis and Enhances Injury at Kidney Repair Phase Post Ischemia–Reperfusion - Wu, Yuanyuan; Zwaini, Zinah D.; Brunskill, Nigel J.; Zhang, Xinyue; Wang, Hui; Chana, Ravinder; Stover, Cordula M.; Yang, Bin (Frontiers in Immunology, 2021)
Properdin, a positive regulator of complement alternative pathway, participates in renal ischaemia-reperfusion (IR) injury, and also acts as a pattern-recognition molecule affecting apoptotic T cell clearance. However, the role of properdin in tubular epithelial cells (TECs) at the repair phase post IR injury is not well defined. This study revealed that properdin knockout (PKO) mice exhibited greater injury in renal function and histology than wild-type (WT) mice post 72-h IR, with more apoptotic cells and macrophages in tubular lumina, increased active caspase-3 and HMGB1, but better histological structure at 24 h. Raised erythropoietin receptor by IR was furthered by PKO and positively correlated with injury and repair markers. Properdin in WT kidneys was also up-regulated by IR, while H2O2-increased properdin in TECs was reduced by its siRNA, with raised HMGB1 and apoptosis. Moreover, the phagocytic ability of WT TECs, analyzed by pHrodo E. coli bioparticles, was promoted by H2O2, but inhibited by PKO. These results were confirmed by counting phagocytosed H2O2-induced apoptotic TECs by in situ end labelling fragmented DNAs, but not affected by additional serum with/without properdin. Taken together, PKO results in impaired phagocytosis at the repair phase post renal IR injury. Properdin locally produced by TECs plays crucial roles in optimizing damaged cells, regulating phagocytic ability of TECs and effectively clearing apoptotic cells and reducing inflammation.